THE ROLE OF CITIZENS IN REGULATORY IMPACT ASSESSMENT OF CONSTITUTIONAL LAW - Kachaset, Kahabordee (Rangsit Journal of Law and Society, 2022)
The need for an analysis of the legal achievement that has been promulgated to the extent of the impact on those involved in society in Thailand It is necessary to review the objectives and principles and rationale of the legislation. and the impact of law enforcement in various dimensions such as social impact economics in terms of the cost-effectiveness of using various public benefits, etc., as well as reviewing the rights and liberties, equality of the people under the constitution human rights According to the rule of law as well, it has been stipulated in the provisions of the Constitution of the Kingdom of Thailand B.E. 2560 for the first time in Article 77 and the Act on Criteria for Draft Laws and Legal Achievement Assessment B.E. This allows citizens of the country to play an active role in legislative and legislative review. The tools and processes for analyzing legal achievement are Therefore, it must be accurate, complete, and have a reliable process. There are standards at the research level to be an important indicator that truly reflects the effectiveness of that law. problem determination Creating a listening process Determination of population groups, population numbers, synthetic analysis of the data obtained. and the selection of information to lead to the correct application The importance of managing the legal achievement analysis process Therefore, it is fundamental that managers must act in accordance with objective research methodology. There is transparency, verifiability of reliable and reliable sources of information. without bias or to determine the outcome to be in a particular direction which is against ethics and social responsibility